2022
DOI: 10.1186/s40662-022-00311-4
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal intraocular lens exchange to monofocal for the management of neuroadaptation failure

Abstract: Background The aim of this study was to evaluate visual, refractive, quality of vision, visual function and satisfaction of multifocal intraocular lens (MF-IOL) exchange with a monofocal IOL (MNF-IOL) in dissatisfied patients following MF-IOL implantation. Methods This was a retrospective case series. Bilateral IOL exchange (MF-IOL to MNF-IOL) was performed in 13 patients (26 eyes) with neuroadaptation failure. Questionnaires including the Quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…If we compare the results of this study with those previously reported in a much smaller series of 5 cases in 2012, where it was found that the main cause for explantation in Spain was IOL dislocation, the present report confirms this finding. However, other different reasons are found in our study such as neuroadaptation failure following MFIOL implantation, a cause that has appeared more recently as a reason for explantation, [26][27][28][29] becoming the third cause of explantation in the second period of our study. In the first decade (2002-2010) there were only 10 cases of explantation related to this cause while in the second decade (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020)(2021) this figure increased to 117 cases.…”
Section: Discussionmentioning
confidence: 68%
“…If we compare the results of this study with those previously reported in a much smaller series of 5 cases in 2012, where it was found that the main cause for explantation in Spain was IOL dislocation, the present report confirms this finding. However, other different reasons are found in our study such as neuroadaptation failure following MFIOL implantation, a cause that has appeared more recently as a reason for explantation, [26][27][28][29] becoming the third cause of explantation in the second period of our study. In the first decade (2002-2010) there were only 10 cases of explantation related to this cause while in the second decade (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020)(2021) this figure increased to 117 cases.…”
Section: Discussionmentioning
confidence: 68%
“…Concomitant DSAEK was performed in patients with clinical edema while IOL explantation was performed when the endothelial cell counts showed a critical decrease. Despite the absence in our series, one emerging indication of IOL exchange is patients' dissatisfaction after multifocal IOL implantation [23,24] We believe that the future trend in our center will also change toward a higher proportion of patients with multifocal IOL exchange as we can see after 2019 in our center.…”
Section: Discussionmentioning
confidence: 73%
“…Despite the absence in our series, one emerging indication of IOL exchange is patients’ dissatisfaction after multifocal IOL implantation [ 23 , 24 ] We believe that the future trend in our center will also change toward a higher proportion of patients with multifocal IOL exchange as we can see after 2019 in our center.…”
Section: Discussionmentioning
confidence: 95%
“…Through the in-depth information mining of many related articles, the study of a discipline's history and development process, and the analysis of the complex cooperative relationship among countries, institutions, and authors, bibliometrics can explore cutting-edge topics in the research eld of interest and predict potential development trends. Despite the e cacy of PIOLs, they still need development because of their many side effects, such as dysphotopsia, halos, glare, and neuroadaptation failure 19,20 . To help researchers understand the history and current research focuses of PIOLs to pursue emerging lines of research more quickly, and to determine possible future development trends, we performed a bibliometric analysis of relevant literature published from January 1, 2000, to November 28, 2022.…”
Section: Introductionmentioning
confidence: 99%